The omnivore's dilemma : a natural history of four meals - Pollan, Michael (Penguin Press, 2006)
What should we have for dinner? When you can eat just about anything nature (or the supermarket) has to offer, deciding what you should eat will inevitably stir anxiety, especially when some of the foods might shorten your life. Today, buffeted by one food fad after another, America is suffering from a national eating disorder. As the cornucopia of the modern American supermarket and fast food outlet confronts us with a bewildering and treacherous landscape, what's at stake becomes not only our own and our children's health, but the health of the environment that sustains life on earth. Pollan follows each of the food chains--industrial food, organic or alternative food, and food we forage ourselves--from the source to the final meal, always emphasizing our coevolutionary relationship with the handful of plant and animal species we depend on. The surprising answers Pollan offers have profound political, economic, psychological, and even moral implications for all of us.--From publisher description.